Heading in soccer: does kinematics of the head-neck-torso alignment influence head acceleration? - Becker, S.; Berger, J.; Ludwig, O.; Günther, D.; Kelm, J.; Fröhlich, M. (Journal of Human Kinetics, 2021)
There is little scientific evidence regarding the cumulative effect of purposeful heading. The head-neck-torso alignment is considered to be of great importance when it comes to minimizing potential risks when heading. Therefore, this study determined the relationship between head-neck-torso alignment (cervical spine, head, thoracic spine) and the acceleration of the head, the relationship between head acceleration and maximum ball speed after head impact and differences between head accelerations throughout different heading approaches (standing, jumping, running). A total of 60 male soccer players (18.9 ± 4.0 years, 177.6 ± 14.9 cm, 73.1 ± 8.6 kg) participated in the study. Head accelerations were measured by a telemetric Noraxon DTS 3D Sensor, whereas angles for the head-neck-torso alignment and ball speed were analyzed with a Qualisys Track Manager program. No relationship at all was found for the standing, jumping and running approaches. Concerning the relationship between head acceleration and maximum ball speed after head impact only for the standing header a significant result was calculated (p = 0.024, R2 = .085). A significant difference in head acceleration (p < .001) was identified between standing, jumping and running headers. To sum up, the relationship between head acceleration and head-neck-torso alignment is more complex than initially assumed and could not be proven in this study. Furthermore first data were generated to check whether the acceleration of the head is a predictor for the resulting maximum ball speed after head impact, but further investigations have to follow. Lastly, we confirmed the results that the head acceleration differs with the approach.